FAKTOR-FAKTOR YANG MEMPENGARUHI BELAJAR TERHADAP PRESTASI SISWA PADA MATA PELAJARAN MATEMATIKA DENGAN MENGGUNAKAN ANALISIS JALUR (Studi Kasus : SMK Negeri 1 Siborongborong) - Mariana . Simanjuntak; Hamidah . Nasution (Universitas Negeri Medan, 2017)
AbstractThis study aims to determine the factors that affect learning in SMK Negeri 1 Siborongborong with test and seek the path coefficient correlation coefficient, determine the causal relationship between exogenous and endogenous variables determine the factors that most influence on student achievement. To answer these objectives researchers using Path Analysis. The data used in this study are primary data and secondary data, where the data obtained from the questionnaires filled by the respondent and then the data is processed using Path Analysis with SPSS 16.0 for windows. The results showed bahwafaktor most influence on student achievement is a great method of learning with the influence of 0,261 and a significant relationship between the factors studied were composed of variations of teachers teaching, interest in learning, learning methods, intelligence and motivation of students studying on student achievement.Keywords: Path Analysis, variation teachers teach, interest in learning, learning methods, learning motivation, intelligence of students.